Lucha, ¿contra qué pobreza? - Iguíñiz Echeverría, Javier (2005)
In this paper we present one of the origins of what is being called today: the “struggle against poverty”. We extract some of the main aspects of the proposal entitled The Concept of Poverty presented by the Chamber of Commerce of the USA in 1965. Our main point is that the nature of the poverty they try to confront corresponds to that existing in that country, and it is quite different from the one most massively present in underdeveloped countries.